MicroRNAs Provide Feedback Regulation of Epithelial‐Mesenchymal Transition Induced by Growth Factors. Issue 1 (28th September 2015) - Qin, Zailong; He, Wei; Tang, Jingqun; Ye, Qiurong; Dang, Wei; Lu, Yuanjun; Wang, Jia; Li, Guiyuan; Yan, Qun; Ma, Jian
Abstract : As regulators in gene expression, microRNAs take part in most biological processes including cell differentiation, apoptosis, cell cycle, and epithelial‐to‐mesenchymal transition (EMT). In order to evaluate their roles in EMT process, microRNA expression profile changes induced by EGF or TGF‐β treatment on nasopharyngeal carcinoma cell HK‐1 were analyzed, and miR‐21, miR‐148a, miR‐505, and miR‐1207‐5p were found to be upregulated in growth factors‐induced EMT process. miR‐21 is already known as an oncogenic miRNA to promote metastasis, however, the exact functions of other three miRNAs in EMT are unclear. To our surprise, we found that miR‐148a, miR‐505, and miR‐1207‐5p can suppress EMT and metastasis phenotypes in HK‐1 cells both in vitro and in vivo, which may relate to their inhibition on EMT and Wnt signaling molecules. MiRNAs confer robustness to biological processes by posttranscriptional repression of key transcriptional programs that are related to previous developmental stages or to alternative cell fates. Our findings indicate that miRNA feedback circuit is tuned to respond to growth factors‐induced EMT, and we suggested a new negative feedback loop which may be an important element of the EMT process and confer biological robustness. J. Cell. Physiol. 230: 120–129, 2016. © 2015 Wiley Periodicals, Inc.